Development of a large animal orthotopic intestinal transplantation model with long-term survival for study of immunologic outcomes - Merl, Sarah; Chen, Bryan; Gunes, M. Esad; Atta, Hussein; Yang, Kryscilla; Ekanayake-Alper, Dilrukshi; Hajosi, Dominik; Huang, Fei; Bhola, Brittany; Patwardhan, Satyajit; Jordache, Philip; Nowak, Greg; et al. (Frontiers in Transplantation, 2024)
Introduction: Intestinal transplantation (ITx) is the last remaining therapy for patients with intestinal failure once parenteral nutrition is no longer an option, however its use is limited by immunological complications, including high rates of rejection and morbidity associated with immunosuppression, such as infection and malignancy. We aimed to develop a large animal model of ITx with which to study the immune response to ITx and to design and test tolerance induction regimens.Methods: Learning from prior complications, we developed and progressively improved both surgical methods for the donor and recipient as well as postoperative management strategies.Methods of stoma generation, bowel positioning, vessel preparation, and fluid management were optimized. The immunosuppression strategy mirrored our clinical regimen.Results: As a result of our modifications, results improved from survival less than 1 month to consistent long-term survival with good graft function. We review several techniques that were developed to avoid pitfalls that were encountered, which can be used to optimize outcomes in this model. Discussion: Achieving long-term survival after swine orthotopic ITx permits immunological analysis and pre-clinical trials in a large animal model of ITx.